A rheological stabilizer, its preparation method and application

CN122941374APending Publication Date: 2026-10-20SHANGHAI BRANCH CHINA OILFIELD SERVICES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611187436.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-06
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

高温环境下,特别是200℃以上条件下油基钻井液的流变性能容易发生劣化,导致携岩能力下降、重晶石沉降和破乳等问题,严重影响钻井效率和安全性

Benefits of technology

(1)本发明通过引入含氟共聚物和复合抗氧化体系(受阻酚类+亚磷酸酯),实现220℃/16h老化后黏度变化率≤10%,动切力保持率≥85%。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure QLYQS_1
    Figure QLYQS_1
Patent Text Reader

Abstract

This invention relates to a rheology stabilizer, its preparation method, and its application. The rheology stabilizer comprises the following components: alkyl quaternary ammonium salt modified nano-silica and a fluorinated copolymer. Through the synergistic effect of the rigid design of the high-temperature resistant copolymer molecular chain, nanoparticle surface modification, and a composite antioxidant system, the rheology stabilizer maintains stable rheological properties at 220℃, significantly improves rock-carrying capacity and demulsification voltage, and simultaneously inhibits barite sedimentation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of oil drilling technology, and in particular to a rheology stabilizer, its preparation method, and its application. Background Technology

[0002] In drilling operations of extended reach wells (tens of thousands of meters), wellbore cleanliness and drilling fluid stability are key technical challenges. Under high-temperature environments, especially above 200°C, the rheological properties of oil-based drilling fluids are prone to deterioration, leading to reduced cutter-carrying capacity, barite settling, and demulsification, severely impacting drilling efficiency and safety. In existing technologies, conventional rheology stabilizers are easily decomposed at high temperatures, causing uncontrolled drilling fluid viscosity and making it difficult to maintain system stability over the long term. Furthermore, high-temperature oxidation reactions accelerate the degradation of drilling fluid properties, affecting demulsification voltage.

[0003] Therefore, there is an urgent need for a solid powder stabilizer that combines high-temperature rheological stability, oxidation resistance, and dispersibility to meet the stringent requirements of ultra-deep well drilling. Summary of the Invention

[0004] To address the aforementioned technical problems, the present invention aims to provide a rheology stabilizer, its preparation method, and its application. The rheology stabilizer, through the synergistic effect of a high-temperature resistant copolymer molecular chain rigidity design, nanoparticle surface modification, and a composite antioxidant system, maintains stable rheological properties at 220℃, significantly improves rock-carrying capacity and demulsification voltage, and simultaneously inhibits barite sedimentation.

[0005] To achieve this objective, the present invention adopts the following technical solution: In a first aspect, the present invention provides a rheology stabilizer comprising the following components: alkyl quaternary ammonium salt modified nano-silica and fluorinated copolymer.

[0006] In this invention, modified nano-silica and fluorinated copolymers form a three-dimensional network structure, which enhances the suspension stability of the rheology stabilizer.

[0007] Preferably, the alkyl quaternary ammonium salt has the structure shown in Formula I: .

[0008] Wherein, R is a C16-C18 (e.g., it can be a C17) alkyl group, X - It can be fluoride ions, chloride ions, bromide ions, or iodide ions.

[0009] Preferably, the alkyl quaternary ammonium salt comprises hexadecyltrimethylammonium bromide and / or octadecyltrimethylammonium chloride.

[0010] Preferably, the comonomers of the fluorinated copolymer include styrene, maleic anhydride, and fluorinated monomers.

[0011] Preferably, the comonomer comprises the following components in parts by weight: 1-4 parts of styrene (e.g., 1.5 parts, 2 parts, 2.5 parts, 2.8 parts, 3 parts, 3.3 parts, or 3.5 parts, etc.), 1 part of maleic anhydride, and 0.5-1 part of fluorinated monomer (e.g., 0.6 parts, 0.7 parts, 0.75 parts, 0.8 parts, or 0.9 parts, etc.).

[0012] In this invention, the amount of fluorinated monomers needs to be controlled within a specific range. Too much fluorinated monomer will lead to polymerization difficulties, poor compatibility and high costs, while too little will result in insufficient high-temperature stability of the copolymer and limited improvement in demulsification voltage.

[0013] Preferably, the fluorinated monomer includes tridecylfluorooctyl acrylate and / or perfluoroalkyl ethyl carboxylate.

[0014] Preferably, the rheology stabilizer comprises the following components in parts by weight: 10-30 parts of alkyl quaternary ammonium salt modified nano silica (e.g., 15 parts, 18 parts, 20 parts, 23 parts or 25 parts, etc.) and 40-60 parts of fluorinated copolymer (e.g., 45 parts, 48 ​​parts, 50 parts, 53 parts or 55 parts, etc.).

[0015] Preferably, the rheology stabilizer further includes an antioxidant.

[0016] Preferably, the antioxidant is present in 5-15 parts by weight, for example, 6 parts, 8 parts, 10 parts, 12 parts or 14 parts, etc.

[0017] Preferably, the antioxidant includes hindered phenolic antioxidants and phosphite antioxidants.

[0018] In this invention, by introducing fluorinated copolymers and a composite antioxidant system (hindered phenols + phosphites), the viscosity change rate after aging at 220℃ for 16h is ≤10%, and the dynamic shear force retention rate is ≥85%.

[0019] Preferably, the mass ratio of the hindered phenolic antioxidant to the phosphite antioxidant is (1.5-2.5):1, for example, it can be 1.6:1, 1.75:1, 1.8:1, 2.0:1, 2.2:1, 2.3:1 or 2.4:1, etc.

[0020] Preferably, the rheology stabilizer further includes an auxiliary dispersant.

[0021] Preferably, the auxiliary dispersant comprises polyether-modified siloxane.

[0022] Preferably, the polyether-modified siloxane comprises an oleophilic polyether-modified siloxane composed of alkyl co-modified polyether siloxane and / or propylene oxide segments.

[0023] Preferably, the auxiliary dispersant is present in 5-15 parts by weight, for example, 6 parts, 7 parts, 7.5 parts, 8 parts, 9 parts, 10 parts or 12 parts, etc.

[0024] Preferably, the preparation method of the fluorinated copolymer includes the following steps: copolymerizing the comonomer of the fluorinated copolymer under the initiation of an initiator to obtain the fluorinated copolymer.

[0025] Preferably, the initiator comprises azobisisobutyronitrile.

[0026] Preferably, the temperature of the copolymerization reaction is 70-90°C, for example, 75°C, 78°C, 80°C, 83°C or 85°C.

[0027] Preferably, the copolymerization reaction takes 6-8 hours, for example, 6.5 hours, 6.8 hours, 7 hours, 7.3 hours or 7.5 hours.

[0028] Preferably, the copolymerization reaction is carried out under a protective gas atmosphere.

[0029] Preferably, the protective gas includes nitrogen or argon.

[0030] Preferably, the preparation method of the alkyl quaternary ammonium salt modified nano silica includes the following steps: mixing and dispersing the alkyl quaternary ammonium salt with nano silica, and modifying it to obtain the alkyl quaternary ammonium salt modified nano silica.

[0031] Preferably, the average particle size of the nano-silica is 10-50 nm, for example, it can be 20 nm, 25 nm, 30 nm, 35 nm or 40 nm.

[0032] Preferably, the dispersion includes ultrasonic dispersion.

[0033] Preferably, the ultrasonic dispersion time is 25-35 min, for example, it can be 26 min, 28 min, 30 min, 32 min or 34 min, etc.

[0034] Preferably, the modification temperature is 55-65℃, for example, it can be 56℃, 58℃, 60℃, 62℃ or 64℃, etc.

[0035] Preferably, the modification time is 2-4 hours, for example, it can be 2.5 hours, 2.8 hours, 3 hours, 3.3 hours or 3.5 hours.

[0036] Preferably, the modified material further includes a post-processing step, the post-processing method comprising centrifugation followed by drying.

[0037] Preferably, the mass ratio of the alkyl quaternary ammonium salt to nano silica is 1:(2-10), for example, it can be 1:2.5, 1:3, 1:4, 1:5, 1:6, 1:7, 1:7.5, 1:8 or 1:9, etc.

[0038] Preferably, the average particle size of the rheology stabilizer is ≤50 μm, for example, it can be 10 μm, 20 μm, 25 μm, 30 μm or 40 μm.

[0039] In a second aspect, the present invention provides a method for preparing a rheology stabilizer as described in the first aspect, the method comprising the following steps: The components of the rheology stabilizer are mixed and ball-milled to obtain the rheology stabilizer.

[0040] Preferably, the rotational speed of the ball mill is 300-500 rpm, for example, it can be 350 rpm, 370 rpm, 400 rpm, 420 rpm or 450 rpm.

[0041] Preferably, the ball milling time is 2-4 hours, for example, it can be 2.5 hours, 2.7 hours, 3 hours, 3.3 hours or 3.5 hours, etc.

[0042] Thirdly, the present invention provides the application of the rheology stabilizer as described in the first aspect in oil-based drilling fluids.

[0043] Preferably, the oil-based drilling fluid includes oil-based drilling fluid for extended reach wells at depths of tens of thousands of meters.

[0044] Compared with the prior art, the present invention has at least the following beneficial effects: (1) By introducing fluorinated copolymers and composite antioxidant systems (hindered phenols + phosphites), this invention achieves a viscosity change rate of ≤10% and a dynamic shear force retention rate of ≥85% after aging at 220℃ / 16h.

[0045] (2) The present invention combines the three-dimensional network structure of modified nano silica (modified with long-chain alkyl quaternary ammonium salt) and fluorinated copolymer to enhance suspension stability, while the auxiliary dispersant (polyether modified siloxane) improves the compatibility of oil-based system.

[0046] (3) The present invention comprehensively optimizes the high-temperature rheology, electrical stability and suspension capacity of oil-based drilling fluids, and is suitable for high-temperature and high-pressure scenarios such as deep wells and shale gas, and has better compatibility with organic soils and emulsifiers.

[0047] (4) The present invention uses non-toxic modified nanomaterials and biodegradable polyether dispersants, taking into account both high-temperature performance and environmental protection requirements, and reducing the cost of waste slurry treatment.

[0048] (5) The rheological stabilizer of the present invention is a solid powder, which can significantly improve the rheological stability, dynamic and static rock-carrying capacity of drilling fluid at high temperature, enhance the wellbore cleaning performance, suppress the risk of barite settling and demulsification of oil-based drilling fluid after long-term static storage, and improve the demulsification voltage. Detailed Implementation

[0049] To facilitate understanding of the present invention, the following embodiments are provided. Those skilled in the art should understand that these embodiments are merely illustrative and should not be construed as limiting the scope of the invention.

[0050] The sources of some of the raw materials used in the preparation of this invention are as follows: The polyether-modified siloxane was purchased from Hangzhou Baode Organosilicon Co., Ltd., with the brand name BD-323.

[0051] The No. 3 white oil was purchased from Sinopec Jingmen Petrochemical and its grade is No. 3 low aromatic white oil.

[0052] The barite was purchased from Puyang Dongsheng Petroleum Drilling and Production Technology Co., Ltd., and its grade is Drilling Fluid Barite (Grade I).

[0053] The organic clay used for preparing oil-based drilling fluid slurry was purchased from Zhejiang Fenghong New Material Co., Ltd., with the grade FHD-130DS.

[0054] Example 1 A rheology stabilizer and its preparation method are provided. The rheology stabilizer comprises the following components in parts by weight: 20 parts of alkyl quaternary ammonium salt modified nano-silica, 50 parts of fluorinated copolymer, 10 parts of composite antioxidant (hindered phenol: phosphite = 7:3), and 10 parts of auxiliary dispersant. The ratio of hindered phenol to phosphite is by mass.

[0055] The preparation method of the rheology stabilizer includes the following steps: (1) Synthesis of fluorinated copolymer: Styrene (60 g), maleic anhydride (20 g), fluorinated monomer tridecyl fluorooctyl acrylate (10 g) and AIBN (1 g) were reacted at 80 °C for 7 hours under nitrogen protection to obtain fluorinated copolymer.

[0056] (2) Nanoparticle modification: 20 g of nano silica was dispersed in 200 mL of ethanol, 5 g of cetyltrimethylammonium bromide was added, and the mixture was reacted at 60 °C for 3 hours. After drying, alkyl quaternary ammonium salt modified nano silica was obtained.

[0057] (3) Ball milling and mixing: Fluorine-containing copolymer, alkyl quaternary ammonium salt modified nano silica, hindered phenol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] pentaerythritol ester, tris(2,4-di-tert-butylphenyl) phosphite and auxiliary dispersant polyether modified siloxane are mixed, ball milled for 3 hours, and sieved to obtain the rheology stabilizer.

[0058] Example 2 A rheology stabilizer and its preparation method are provided. The rheology stabilizer comprises the following components in parts by weight: 25 parts of alkyl quaternary ammonium salt modified nano-silica, 55 parts of fluorinated copolymer, 8 parts of composite antioxidant (hindered phenol: phosphite = 6:4), and 12 parts of auxiliary dispersant. The ratio of hindered phenol to phosphite is by mass.

[0059] The preparation method of the rheology stabilizer includes the following steps: (1) Synthesis of fluorinated copolymer: Styrene (60 g), maleic anhydride (20 g), fluorinated monomer tridecyl fluorooctyl acrylate (16 g) and AIBN (1.06 g) were reacted at 80 °C for 7 hours under nitrogen protection to obtain fluorinated copolymer.

[0060] (2) Nanoparticle modification: 20 g of nano silica was dispersed in 200 mL of ethanol, 8 g of cetyltrimethylammonium bromide was added, and the mixture was reacted at 60 °C for 4 hours. After drying, alkyl quaternary ammonium salt modified nano silica was obtained.

[0061] (3) Ball milling and mixing: Fluorine-containing copolymer, alkyl quaternary ammonium salt modified nano silica, hindered phenol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] pentaerythritol ester, tris(2,4-di-tert-butylphenyl) phosphite and auxiliary dispersant polyether modified siloxane are mixed, ball milled for 4 hours, and sieved to obtain the rheology stabilizer.

[0062] Example 3 A rheology stabilizer and its preparation method are provided. The rheology stabilizer comprises the following components in parts by weight: 15 parts of alkyl quaternary ammonium salt modified nano-silica, 40 parts of fluorinated copolymer, 5 parts of composite antioxidant (hindered phenol: phosphite = 6:4), and 5 parts of auxiliary dispersant. The ratio of hindered phenol to phosphite is by mass.

[0063] The preparation method of the rheology stabilizer includes the following steps: (1) Synthesis of fluorinated copolymer: Styrene (30 g), maleic anhydride (20 g), fluorinated monomer tridecyl fluorooctyl acrylate (10 g) and AIBN (0.66 g) were reacted at 80 °C for 7 hours under nitrogen protection to obtain fluorinated copolymer.

[0064] (2) Nanoparticle modification: 20 g of nano silica was dispersed in 200 mL of ethanol, 2 g of cetyltrimethylammonium bromide was added, and the mixture was reacted at 60 °C for 1 hour. After drying, alkyl quaternary ammonium salt modified nano silica was obtained.

[0065] (3) Ball milling and mixing: Fluorine-containing copolymer, alkyl quaternary ammonium salt modified nano silica, hindered phenol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] pentaerythritol ester, tris(2,4-di-tert-butylphenyl) phosphite and auxiliary dispersant polyether modified siloxane are mixed, ball milled for 2 hours, and sieved to obtain the rheology stabilizer.

[0066] Example 4 A rheology stabilizer and its preparation method are provided, the only difference from Example 1 is that the amount of the fluorinated monomer used in step (1) is 25 g.

[0067] Example 5 A rheology stabilizer and its preparation method are provided. The only difference from Example 1 is that the amount of the fluorinated monomer used in step (1) is 5 g.

[0068] Example 6 A rheology stabilizer and its preparation method are provided, the only difference from Example 1 is that the composite antioxidant has a weight ratio of 0 parts.

[0069] Comparative Example 1 A rheology stabilizer and its preparation method are provided, the only difference from Example 1 is that the alkyl quaternary ammonium salt modified nano silica is replaced with the same weight parts of unmodified nano silica.

[0070] Specifically, the preparation method of the rheology stabilizer includes the following steps: (1) Synthesis of fluorinated copolymer: Styrene (60 g), maleic anhydride (20 g), fluorinated monomer tridecyl fluorooctyl acrylate (10 g) and AIBN (1 g) were reacted at 80 °C for 7 hours under nitrogen protection to obtain fluorinated copolymer.

[0071] (2) Ball milling and mixing: Fluorine-containing copolymer, nano silica, hindered phenol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] pentaerythritol ester, tris(2,4-di-tert-butylphenyl) phosphite and auxiliary dispersant polyether modified siloxane are mixed, ball milled for 3 hours, and sieved to obtain the rheology stabilizer.

[0072] Comparative Example 2 A rheology stabilizer and its preparation method are provided, the only difference from Example 1 is that the fluorinated copolymer is replaced with the same number of parts by weight of a non-fluorinated copolymer.

[0073] Specifically, the preparation method of the rheology stabilizer includes the following steps: (1) Synthesis of fluorine-free copolymer: Styrene (67.5 g), maleic anhydride (22.5 g) and AIBN (1 g) were reacted at 80 °C for 7 hours under nitrogen protection to obtain fluorine-free copolymer.

[0074] (2) Nanoparticle modification: 20 g of nano silica was dispersed in 200 mL of ethanol, 5 g of cetyltrimethylammonium bromide was added, and the mixture was reacted at 60 °C for 3 hours. After drying, alkyl quaternary ammonium salt modified nano silica was obtained.

[0075] (3) Ball milling and mixing: The fluorine-free copolymer, alkyl quaternary ammonium salt modified nano silica, hindered phenol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] pentaerythritol ester, tris(2,4-di-tert-butylphenyl) phosphite and auxiliary dispersant polyether modified siloxane are mixed, ball milled for 3 hours, and sieved to obtain the rheology stabilizer.

[0076] Application Example 1-6, Comparative Application Example 1-2 A method for preparing an oil-based drilling fluid is provided. The method for preparing the oil-based drilling fluid includes the following steps: 243 mL of No. 3 white oil is poured into a high-speed stirring cup; 8.55 g of MOEMUL (purchased from CNOOC Oilfield Services Limited) and 7.15 g of MOCOAT (purchased from CNOOC Oilfield Services Limited) as the primary emulsifier for oil-based drilling fluid are weighed and added to the high-speed stirring cup, and stirred at 10000 r / min for 5 min; 46 mL of a pre-prepared 25% CaCl2 aqueous solution is slowly poured in under stirring conditions, and stirred at 10000 r / min for 20 min; then 8.00 g of organic clay for oil-based drilling fluid slurry preparation is added, and stirred at 10000 r / min for 20 min; 15.00 g of MOTEX (purchased from CNOOC Oilfield Services Limited) and 6.00 g of calcium oxide are added as a filtration reducer for oil-based drilling fluid, and stirred at 10000 r / min for 10 min; then 400... g of barite was stirred at 10000 r / min for 20 min, and then the rheology stabilizers of Examples 1-6 and Comparative Examples 1-2 were added to obtain the oil-based drilling fluid. The mass percentage of the rheology stabilizer in the oil-based drilling fluid was 1%.

[0077] Comparative Application Example 3 An oil-based drilling fluid and its preparation method are provided, the only difference from Application Example 1 being that the oil-based drilling fluid is a base slurry without the addition of rheology stabilizers.

[0078] Specifically, the preparation method of the oil-based drilling fluid includes the following steps: Measure 243 mL of No. 3 white oil and pour it into a high-speed stirring cup; weigh 8.55 g of the main emulsifier MOEMUL (purchased from CNOOC Oilfield Services Limited) and 7.15 g of the auxiliary emulsifier MOCOAT (purchased from CNOOC Oilfield Services Limited) for oil-based drilling fluid and add them to the high-speed stirring cup, stirring at 10000 r / min for 5 min; under stirring conditions, slowly pour in 46 mL of a pre-prepared 25% CaCl2 aqueous solution, stirring at 10000 r / min for 20 min; then add 8.00 g of organic clay for oil-based drilling fluid slurry preparation, stirring at 10000 r / min for 20 min; add 15.00 g of filtration loss reducer MOTEX (purchased from CNOOC Oilfield Services Limited) and 6.00 g of calcium oxide for oil-based drilling fluid, stirring at 10000 r / min for 10 min; then add 400 g of barite, stirring at 10000 r / min... The oil-based drilling fluid was obtained by high-speed stirring at r / min for 20 min.

[0079] Test methods The oil-based drilling fluids from Application Examples 1-6 and Comparative Application Examples 1-3 were placed in an aging tank, which was then placed in a hot-rolling furnace at 220°C for 16 hours. After cooling, the oil-based drilling fluids were removed and their rheological properties, demulsification voltage, filtrate loss, and sedimentation factor were determined according to the method specified in GB / T 16783.2. A sedimentation factor SF = ρ_lower / (ρ_upper + ρ_lower) ≤ 0.52 was considered to indicate good sedimentation stability, where ρ is the drilling fluid density.

[0080] The test results are shown in Table 1.

[0081] Table 1 The test results show that: (1) As can be seen from Application Examples 1 to 6, the present invention enhances the suspension stability of the rheology stabilizer by forming a three-dimensional network structure of modified nano-silica and fluorinated copolymer.

[0082] Application Example 1 is the best application example of the present invention. After adding the rheological stabilizer, the dynamic rock-carrying capacity of the oil-based drilling fluid after hot rolling aging at 220°C is greatly improved. The dynamic shear force increases from 3 Pa to 15 Pa, an increase of 400%, and the dynamic-to-plastic ratio increases from 0.13 to 0.56, an increase of 330%. The static suspension capacity parameter 3, rotational speed, increases from 2 to 11, an increase of 450%. The sedimentation factor is 0.513, which is less than 0.52, indicating good barite sedimentation stability. The demulsification voltage increases from 930V to 1520V, further improving the emulsification stability.

[0083] (2) By comparing Application Example 1 with Application Examples 4-5, it can be seen that the present invention improves the performance of the rheology stabilizer by further limiting the amount of fluorinated monomer in the fluorinated copolymer.

[0084] A comparison of Application Example 1 and Application Example 6 shows that the present invention improves the performance of the rheology stabilizer by further using a combination of a composite antioxidant system and a fluorinated copolymer.

[0085] (3) By comparing Application Example 1 with Comparative Application Example 1-2, it can be seen that if the nano-silica is not modified with alkyl quaternary ammonium salt or the copolymer monomer does not contain fluorine-containing monomers, the performance of the rheology stabilizer will be significantly worse.

[0086] In summary, the rheology stabilizer of the present invention maintains stable rheological properties at a high temperature of 220°C through the synergistic effect of rigid design of high-temperature resistant copolymer molecular chains, surface modification of nanoparticles, and composite antioxidant system, significantly improving rock carrying capacity and demulsification voltage, while inhibiting barite sedimentation.

[0087] The applicant declares that the above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.

Claims

1. A rheology stabilizer, characterized in that, The rheology stabilizer comprises the following components: alkyl quaternary ammonium salt modified nano-silica and fluorine-containing copolymer.

2. The rheology stabilizer according to claim 1, characterized in that, The alkyl quaternary ammonium salt has the structure shown in Formula I: ; Wherein, R is a C16-C18 alkyl group, X - It can be fluoride ions, chloride ions, bromide ions, or iodide ions; Preferably, the alkyl quaternary ammonium salt comprises hexadecyltrimethylammonium bromide and / or octadecyltrimethylammonium chloride.

3. The rheology stabilizer according to claim 1 or 2, characterized in that, The comonomers of the fluorinated copolymer include styrene, maleic anhydride, and fluorinated monomers; Preferably, the comonomer comprises the following components in parts by weight: 1-4 parts styrene, 1 part maleic anhydride, and 0.5-1 part fluorinated monomer; Preferably, the fluorinated monomer includes tridecylfluorooctyl acrylate and / or perfluoroalkyl ethyl carboxylate.

4. The rheology stabilizer according to any one of claims 1-3, characterized in that, The rheology stabilizer comprises the following components in parts by weight: 10-30 parts of alkyl quaternary ammonium salt modified nano silica and 40-60 parts of fluorinated copolymer.

5. The rheology stabilizer according to any one of claims 1-4, characterized in that, The rheology stabilizer also includes an antioxidant; Preferably, the antioxidant is present in 5-15 parts by weight; Preferably, the antioxidant includes hindered phenolic antioxidants and phosphite antioxidants; Preferably, the mass ratio of the hindered phenolic antioxidant to the phosphite antioxidant is (1.5-2.5):

1.

6. The rheology stabilizer according to any one of claims 1-5, characterized in that, The rheology stabilizer also includes an auxiliary dispersant; Preferably, the auxiliary dispersant comprises a polyether-modified siloxane; Preferably, the auxiliary dispersant is present in 5-15 parts by weight.

7. The rheology stabilizer according to any one of claims 1-6, characterized in that, The preparation method of the fluorinated copolymer includes the following steps: copolymerizing the comonomer of the fluorinated copolymer under the initiation of an initiator to obtain the fluorinated copolymer; Preferably, the initiator comprises azobisisobutyronitrile; Preferably, the copolymerization reaction is carried out at a temperature of 70-90°C; Preferably, the copolymerization reaction is carried out under a protective gas atmosphere.

8. The rheology stabilizer according to any one of claims 1-7, characterized in that, The preparation method of the alkyl quaternary ammonium salt modified nano silica includes the following steps: mixing and dispersing the alkyl quaternary ammonium salt with nano silica, and modifying it to obtain the alkyl quaternary ammonium salt modified nano silica; Preferably, the dispersion includes ultrasonic dispersion; Preferably, the mass ratio of the alkyl quaternary ammonium salt to nano-silica is 1:(2-10).

9. A method for preparing a rheology stabilizer as described in any one of claims 1-8, characterized in that, The preparation method includes the following steps: The components of the rheology stabilizer are mixed and ball-milled to obtain the rheology stabilizer.

10. The application of a rheology stabilizer as described in any one of claims 1-8 in an oil-based drilling fluid.